An additional record of the non-indigenous species (NIS) Seriola fasciata from the southern coast of Sicily (Central Mediterranean Sea) - Geraci, Michele Luca; Falsone, Fabio; Scannella, Danilo; Vitale, Sergio (2020)
An additional record of the non-indigenous species (NIS) Seriola fasciata from the southern coast of Sicily (Central Mediterranean Sea) is here described in this note. The catch record is the first in the area and confirms the key role of the area for NIS spreading. In addition, an updated map of its spatial distribution is provided as well as a discussion on the possible misidentification and competition with the native greater amberjack Seriola dumerili.
U ovoj je bilješci opisan dodatni nalaz o vrsti Seriola fasciata s južne obale Sicilije (Sredozemno more). Ovaj nalaz je prvi na tom području i potvrđuje ključnu ulogu područja za širenje stranih vrsta (NIS). Osim toga, prikazana je ažurirana karta prostorne raspodjele vrste Seriola fasciata, kao i rasprava o mogućoj pogrešnoj identifikaciji i kompeticiji s vrstom Seriola dumerili.
Bibliografija: str. 227-229.
Summary ; Sažetak.
Keywords: Morske ribe -- Seriola fasciata -- Biološka raznolikost -- Prostorna rasprostranjenost; Sicilijski tjesnac -- Sredozemno more